TRANSNATIONAL TRANSLATION OF TAIWANESE AND INDONESIAN TRADITIONAL STORIES FOR GLOBAL CITIZENSHIP - Novita Dewi (International Journal of Humanity Studies (IJHS), 2018)
In order to interact and work with diverse communities in this deeply interconnected world and to help solve such global issues as human rights abuse, ecological damage, economic poverty and extremism, we need to continually recognize and exchange values/perspectives across cultures and boundaries. Border-crossing is a complex but necessary web of interactions and dependencies among nations to create global peace and justice. Taiwan-Indonesia border crossing is insufficient, given that no formal diplomatic relation exists between the two countries excepting the informal such as trade and investment, people-to-people relations, education and popular culture industry. Taiwan and Indonesia similarly shared long history of nationalism, anti-communism, and democratization, but it remains under studied how these historical comparisons are reflected through literature. This paper will argue that transnational translation of literature can connect and define both nations better so as to enhance global connectedness. Thus, the crossing of the cultural boundaries by Taiwanese and Indonesian co-cultures through the translation of diverse literary works may give hope for future development of a mutual, emphatic understanding of each others cultures.